The Effectiveness of the Health Promotion Program for the Development of Elderly Health literacy and Quality of Life in the Princess Maha Chakri Sirindhorn Medical Center’s Area of Responsibility - Visuttranukul, Ammara; Panyasaisophon, Thanakorn; Visuttipukdee, Kamonphat; Thamrongworakun, Phitsaran; Chanpleng, Panat (Journal of Public Health and Development, 2021)
This quasi-experimental research study was conducted to measure the effectiveness of the health promotion program for the development of elderly health literacy and elderly quality of life in the HRH Princess Maha Chakri Sirindhorn Medical Center's area of responsibility. The sample consisted of elderly males and females living in the Ongkharak district, Nakhon Nayok Province. These individuals were divided into a control and an experimental group, each consisting of 46 people who were selected by the specified criteria. The health promotion program was developed by applying the quality of life concept together with health literacy, the World Health Organization (WHO)'s Quality of Life Assessment (WHOQOL-BREF-THAI), and the Health Literacy and Behavioral Evaluation according to the 3E2S of the Health Education Division, Thailand’s Ministry of Public Health. The statistics measured in this study were percentage, mean score, standard deviation, and t-test. The results indicated that, after completion of the health promotion program, the members of the experimental group had a better quality of life compared to the control group, statistically significant at 0.01 level. Also, after completing the health promotion program, the members of the experimental group had better health literacy and health behavior according to the 3E2S than the control group, statistically significant at the level of 0.01.